Fortification of cut semi-finished product using oat flour and dry demineralized milk whey - Biryuk, Yulia; Chernyushok, Olga (My University, 2023)
The object of research was selected chopped meats semi-finished products, which which are proposed to be enriched by adding dry milk whey and oat flour to the recipe. The expediency of using ingredients is substantiated and useful substances contained in dairy and vegetable raw materials are given. Об’єктом дослідження обрано посічені м’ясні напівфабрикати, які збагачено, за допомогою внесення до рецептури сухої молочної сироватки та вівсяного борошна. Обгрунтовано доцільність використання інгредієнтів та наведено корисні речовини, які містяться у молочній і рослинній сировині.
Keywords: кафедра технології м’яса і м’ясних продуктів; quality indicators; fortified; dry milk whey; oat flour; semi-finished products; meat; sample; recipe; показники якості; суха молочна сироватка; вівсяне борошно; напівфабрикати; м'ясо; зразок; рецептура